Local Cancer Recurrence: The Realities, Challenges, and Opportunities for New Therapies. (17th October 2018) - Mahvi, David A.; Liu, Rong; Grinstaff, Mark W.; Colson, Yolonda L.; Raut, Chandrajit P.
Abstract: Locoregional recurrence negatively impacts both long‐term survival and quality of life for several malignancies. For appropriate‐risk patients with an isolated, resectable, local recurrence, surgery represents the only potentially curative therapy. However, oncologic outcomes remain inferior for patients with locally recurrent disease even after macroscopically complete resection. Unfortunately, these operations are often extensive, with significant perioperative morbidity and mortality. This review highlights selected malignancies (mesothelioma, sarcoma, lung cancer, breast cancer, rectal cancer, and peritoneal surface malignancies) in which surgical resection is a key treatment modality and local recurrence plays a significant role in overall oncologic outcome with regard to survival and quality of life. For each type of cancer, the current, state‐of‐the‐art treatment strategies and their outcomes are assessed. The need for additional therapeutic options is presented given the limitations of the current standard therapies. New and emerging treatment modalities, including polymer films and nanoparticles, are highlighted as potential future solutions for both prevention and treatment of locally recurrent cancers. Finally, the authors identify additional clinical and research opportunities and propose future research strategies based on the various patterns of local recurrence among the different cancers.